Targeted screening for genetic haemochromatosis: a combined phenotype/genotype approach. Issue 5 (27th April 2006) - Bhavnani, M; Lloyd, D; Marples, J; Pendry, K; Worwood, M
Abstract : Objective: To evaluate the clinical utility of a targeted screening approach for the detection of genetic haemochromatosis. Methods: Screening by measuring fasting serum transferrin saturation (TS) and gene testing was carried out in patients in whom a raised serum alanine amino transferase (ALT) activity and raised random serum TS had been found on routine blood testing. Results: During the 29 month study period, 32 patients homozygous for the C282Y genotype were detected from a catchment population of 330 000 by screening blood samples referred initially for routine laboratory liver function tests. By comparison, during the same period of time and within the same population, only seven patients were found by clinical suspicion alone. The patients in the study, after treatment by venesection, have shown both clinical and biochemical improvement. Conclusions: The study shows that from a population of patients in whom a routine liver function profile had been requested, it is possible to detect subjects homozygous for the C282Y HFE genotype who have clinical or biochemical markers of iron overload.